EGFR is a potential dual molecular target for cancer and Alzheimer’s disease - Choi, Hee-Jeong; Jeong, Yoo Joo; Kim, Jieun; Hoe, Hyang-Sook (Frontiers in Pharmacology, 2023)
Many researchers are attempting to identify drugs that can be repurposed as effective therapies for Alzheimer’s disease (AD). Several recent studies have highlighted epidermal growth factor receptor (EGFR) inhibitors approved for use as anti-cancer drugs as potential candidates for repurposing as AD therapeutics. In cancer, EGFR inhibitors target cell proliferation and angiogenesis, and studies in AD mouse models have shown that EGFR inhibitors can attenuate amyloid-beta (Aβ) pathology and improve cognitive function. In this review, we discuss the different functions of EGFR in cancer and AD and the potential of EGFR as a dual molecular target for AD diseases. In addition, we describe the effects of anti-cancer EGFR tyrosine kinase inhibitors (TKIs) on AD pathology and their prospects as therapeutic interventions for AD. By summarizing the physiological functions of EGFR in cancer and AD, this review emphasizes the significance of EGFR as an important molecular target for these diseases.